2003
DOI: 10.1110/ps.03102403
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence and crystal structure of BaP1, a metalloproteinase from Bothrops asper snake venom that exerts multiple tissue‐damaging activities

Abstract: BaP1 is a 22.7-kD P-I-type zinc-dependent metalloproteinase isolated from the venom of the snake Bothrops asper, a medically relevant species in Central America. This enzyme exerts multiple tissue-damaging activities, including hemorrhage, myonecrosis, dermonecrosis, blistering, and edema. BaP1 is a single chain of 202 amino acids that shows highest sequence identity with metalloproteinases isolated from the venoms of snakes of the subfamily Crotalinae. It has six Cys residues involved in three disulfide bridg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 48 publications
(111 reference statements)
1
70
1
7
Order By: Relevance
“…Similar observations were seen for other crystal structures of non-hemorrhagic metalloproteinases including the fibrinogenolases (TM-1, TM-2, and TM-3) from Taiwan Habu [58]. Indeed, these three non-hemorrhagic metalloproteinases contain a very robust basic field potential surface whereas acutolysin C and Bap1 from Bothrops asper, two weakly hemorrhagic metalloproteinases [53], show energy landscapes with mix polarities in that they contain a highly basic field potential landscape at the N-terminal region and an acidic field potential energy landscape near the catalytic site (data not shown). In further agreement with this view, the intensity of the negative field potential maps surrounding the Zn +2 binding domain and the Met turn for each of the C. s. scutulatus metalloproteinases correlated with hemorrhagic potency [32] in the following manner: atrolysin C> GP1> GP4> GP3> GP2> adamalysin II.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similar observations were seen for other crystal structures of non-hemorrhagic metalloproteinases including the fibrinogenolases (TM-1, TM-2, and TM-3) from Taiwan Habu [58]. Indeed, these three non-hemorrhagic metalloproteinases contain a very robust basic field potential surface whereas acutolysin C and Bap1 from Bothrops asper, two weakly hemorrhagic metalloproteinases [53], show energy landscapes with mix polarities in that they contain a highly basic field potential landscape at the N-terminal region and an acidic field potential energy landscape near the catalytic site (data not shown). In further agreement with this view, the intensity of the negative field potential maps surrounding the Zn +2 binding domain and the Met turn for each of the C. s. scutulatus metalloproteinases correlated with hemorrhagic potency [32] in the following manner: atrolysin C> GP1> GP4> GP3> GP2> adamalysin II.…”
Section: Discussionsupporting
confidence: 83%
“…For instance, it has been reported that the interconnecting loop that follows the Met turn, which also contains the S'1-specificity pocket, is remarkably more flexible in non-hemorrhagic metalloproteinases compared to hemorrhagic metalloproteinases [52]. In agreement with this observation [52,53], the C. s. scutulatus metalloproteinases belonging to the non-hemorrhagic group of metalloproteinases (GP2) contained a much more dynamic S'1-pocket than the strongly or weakly hemorrhagic groups (GP1 and GP4) as measured by the standard deviations of the angular shift over time (GP1: ±4.04 • , GP2: ±6.72 • , GP3: ±6.73 • , GP4: ±4.90 • ).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Este espectro foi analisado utilizando a técnica de bioinformática em MALDI TOF, com o programa Mascot Search Results (Matrix Science), o qual revelou score significativo (score de 80 e p<0.05) com a metaloprotease não hemorrágica BmooMPα-I, proveniente também da peçonha da serpente do gênero Bothrops moojeni (BERNADES et al, 2008 (WATANABE et al, 2003). Desta maneira, pode-se afirmar, de acordo com a classificação das metaloproteases apresentadas por FOX; SERRANO, (2010), que BthMP é uma metaloprotease da classe P-I.…”
Section: Resultsunclassified
“…A number of hemorrhagic SVMPs have been isolated from B. asper venom. The most abundant SVMP is the P-I enzyme BaP1 (Gutié rrez et al, 1995;Watanabe et al, 2003), although the most potent hemorrhagic enzymes are the high molecular mass P-III SVMPs BaH1 and BaH4 (Borkow et al, 1993;Franceschi et al, 2000). Moreover, the effectiveness of clodronate and doxycycline to inhibit coagulant activity of B. asper venom on plasma and defibrinogenating activity (in the case of doxycycline) can also be explained by the observation that SVMPs are the most important coagulant components in this venom (Rucavado et al, 2004).…”
Section: Discussionmentioning
confidence: 99%